Enhanced thermal radiation blocking and high temperature stability of nanostructured YSZ thermal barrier coatings through carbon film coating - Liu-Chao Zhang; Fa Luo; Ying-Ying Zhou; Ya-Ru Cao; Jun-Jie Yang; Yu-Qin Li; Yu-Chang Qing (Journal of Advanced Ceramics)
The semi-transparency to thermal radiation, coupled with low nanoparticle retention and formation of semi-melted particles during plasma spraying, significantly limits the high-temperature application of nanostructured yttria stabilized zirconia (YSZ) (nYSZ) thermal barrier coatings. To address these challenges, this study introduces an innovative approach that involves coating nanoparticles with carbon films to prevent them from melting and merging during the plasma spraying process. This method substantially increases the nanoparticle content within the coating, and nanopores formed at the nanoparticle surfaces when the carbon film is removed at 800 °C. These nanopores, in combination with nanoparticles, enhance thermal radiation scattering, improving the scattering coefficient and thermal radiation blocking capability of the coating. In contrast to that of conventional thermal barrier coatings (TBCs) of YSZ, the simulated temperature of the substrate under service conditions decreases by up to 26.26 K due to decreased radiative heat transfer and by 111.2 K when the thermal conductivity is reduced. Additionally, the scattering coefficients remain stable within the 1–5 μm range even after heat treatment at 1300 °C for 100 h, as the coarsened nanoparticle size approaches the wavelength of thermal radiation. Thus, nYSZ TBCs with enhanced thermal radiation blocking ability and high temperature stability can be created by this approach for higher temperature applications.